Hambatan Keberlanjutan Usaha Kecil dan Menengah: Tinjauan Literatur - Ahmad Faridi; Unang Toto Handiman; Dinar Nur Affini; Herdiyanto Herdiyanto; E Rochaeti; Ahmad Hidayat Sutawijaya (Universitas Mercu Buana, 2022)
The purpose of this article is to analyze the barriers faced by small and medium-sized enterprises (SMEs) when implementing initiatives for sustainable development. For this purpose, a search equation was designed, and the 54 articles were the highest cited from the search results via the Publish or Perish tool between 2015 and December 2021. The criteria selected for article analysis were article title, article year, abstract, and keywords. The research methodology uses a three-stage systematic literature review. The results of this study are the barriers to sustainability for SMEs. The most common barriers are lack of resources, high initial capital costs to implement sustainability measures, lack of expertise, risk aversion, short-term planning, technological complexity, waste of time. This research can identify various types of barriers to sustainable SMEs.